Deteksi Tepi Menggunakan Metode Laplacian of Gaussian Pada Citra Bola Futsal - Prasetyo, Endri Dwi (TIN: Terapan Informatika Nusantara, 2020)
A ball is a round object that is used as a sport or game. Generally the ball is filled with air. There are various kinds of balls, one of which is a futsal ball. A futsal ball is the same ball as a soccer ball but what distinguishes it is the size of the ball, the weight of the ball and its texture. Often times new futsal balls cannot be played because of the wrong size of the ball or the ball is defective (propeller ball). As a result, when a tournament or league is held, in the middle of a match players often ask for the replacement of the ball with the referee because the ball is not comfortable. The propeller ball is often an obstacle for players. This makes it difficult for the players to control the ball, pass and kick the ball. Therefore it is necessary to conduct research to identify ball defects using its image